Disturbances in groundwater chemical parameters related to seismic and volcanic activity in Kamchatka (Russia) - Biagi P. F.; Castellana L.; Piccolo R.; Minafra A.; Maggipinto G.; Capozzi V.; Perna G.; Khatkevich Y. M.; Gordeev E. I.; ERMINI, ANITA (Natural Hazards and Earth System Sciences, 2004)
Starting from 1992 geochemical data are being collected with a mean sampling frequency of three days in the form of the pH value and of the most common ions and gases in the groundwater in one deep well located in Petropavlovsk, the capital city of Kamchatka (Russia). On 1 January 1996 a strong eruption started from the Karymsky volcano, that is located about 100 krn far from the well, in the north-northeastern direction. At the same time, a large earthquake (M=6.9) occurred in the Karymsky area. On 5 December 1997 a very large earthquake (M=7.7) occurred offshore, at a distance of 350 km from the well and towards the same direction. The analysis of the geochernical data shows clear variations in the raw temporal trends on both cases. For the first event, a clear premonitory phase appeared; for the second one, some pre-seismic variations could be revealed but permanent modifications of the chemistry of the water subsequent to the earthquake are very clear. In both cases the feature of the geochernical variations is consistent with an afflux of new water in the aquifer connected with the well and with an escape of the Carbon dioxide gas from the ground in different directions. A schematic model able to justify such a phenomenology and the connections of the geochernical variations with the previous tectonic activities is proposed.